1998
DOI: 10.1136/jnnp.64.5.624
|View full text |Cite
|
Sign up to set email alerts
|

Early transoesophageal echocardiography in cryptogenic and lacunar stroke and transient ischaemic attack

Abstract: Atrial thrombi were found in one patient with a cryptogenic stroke (2.32% of cryptogenic events; 95% confidence interval 0.06-12.29), whereas SEC was found in five patients (7.7% overall), two with a lacunar and three with a cryptogenic stroke. Conclusions-An early TOE does not seem to increase substantially the detection of atrial thrombi or SEC in patients with a first stroke or transient ischaemic attack of cryptogenic or lacunar nature. Therefore, this examination can be carried out when the patients' cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
1
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 34 publications
3
16
1
1
Order By: Relevance
“…A total of 260 articles were identified in the initial search, of which 27 (n = 5,653) met our eligibility criteria, [23][24][25][26][27][28][29][30][31][32][33][34][35][36][38][39][40][41]7,[42][43][44][45]11,[46][47][48][49][50][51][52] including 18 subcohorts in group A (b55 years, n = 2,360) and 20 subcohorts in group B (≥55 years or age unselected, n = 3,293). online Appendix Supplementary Table II summarizes the characteristics of the study populations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 260 articles were identified in the initial search, of which 27 (n = 5,653) met our eligibility criteria, [23][24][25][26][27][28][29][30][31][32][33][34][35][36][38][39][40][41]7,[42][43][44][45]11,[46][47][48][49][50][51][52] including 18 subcohorts in group A (b55 years, n = 2,360) and 20 subcohorts in group B (≥55 years or age unselected, n = 3,293). online Appendix Supplementary Table II summarizes the characteristics of the study populations.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies (n = 591) reported on the proportion of patients who were commenced on oral anticoagulant therapy following the results of TEE, including 0%, 37 2.3%, 11 6.0%, 43 11.0%, 23 and 30.7% 24 of patients. Left atrial thrombus, SEC, PFO, PFO with ASA, and aortic plaques were the most commonly reported indications for introduction of oral anticoagulation after TEE results.…”
Section: Change In Management Based On Tee Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immediate echocardiography yields a low incidence of findings: In 65 patients with cryptogenic stroke, TIA, or lacunar stroke, TEE performed within 3 days of presentation yielded an atrial thrombus in 1 patient, and 5 had spontaneous echo contrast. 160 The echocardiographic method used is important. TEE is more sensitive than TTE for atheroma of the aortic arch and abnormalities of the interatrial septum (eg, atrial septal aneurysm, PFO, atrial septal defect), atrial thrombi, and valvular disease.…”
Section: Cardiac and Other Testingmentioning
confidence: 99%
“…Knowledge of the relationship between echocardiographic smoke and intracardiac thrombus and the nature of the smoke may help the management of patients with cerebral embolism when the need for anticoagulant or antiplatelet aggregatory agent is to be considered. 11 While the association between ischemic stroke and cardiac thrombi and spontaneous echo contrast has been under investigation, [12][13][14][15] several methods have been used to investigate the pathogenesis of spontaneous contrast. 2,5,16 In the previous studies, although blood stasis, 16 platelet aggregation, 17 red blood cell (RBC) coagulation, 18 and flow-related interaction of RBCs and plasma have been implicated in such echogenicity, the mechanism responsible for the formation of echocardiographic smoke is still not fully understood.…”
mentioning
confidence: 99%